Description of new genus Baikalozercon (Acari: Mesostigmata: Zerconidae) with two new species from South Siberia Mountains (Russia) - Marchenko, Irina I. (Zootaxa, 2022)
This paper describes a new genus and two new species of mites in the family Zerconidae collected from litter and soil in the South Siberia Mountains. Baikalozercon gen. nov. is described to accommodate two new species B. dracunculus sp. nov. and B. irbis sp. nov. on the basis of adults specimens and immature stages. The new genus is characterised by unique characters such as very large size of idiosoma (900–1000 µm length); long peritremes in adults reaching to coxae I; sexual dimorphism of male gnathosomal structures; modified fixed digit of chelicerae with extended apical edge and large apical outgrowth; a pair of massive subcapitular denticles located between h3 and pc setae in B. dracunculus sp. nov.; and modified setae on legs II.